2011
DOI: 10.1590/s1020-49892011000600013
|View full text |Cite
|
Sign up to set email alerts
|

Panacéias disseminadas pela Internet e pacientes vulneráveis: como conter um mercado de ilusões?

Abstract: This article discusses the proliferation of medical quackery and fraud appearing and disappearing daily on the Internet. The customers of these scams, made vulnerable by disease or the prospect of death, use the Internet to buy products that would probably be ignored in other contexts. This vulnerability is linked to strenuous physical demands that compromise the ability to make decisions. The attempt to control the phenomenon of fraud as strictly rational, without taking into account the vulnerability of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, like any technological advance, there are unintended consequences of this rapidly available information. Studies have found chat rooms used for discussion of benzydamine abuse to induce hallucinations and fraudulent websites often target uneducated populations with desperate medical conditions (SOUZA, 2008;VASCONCELLOS-SILVA, 2011). …”
Section: Literature Reviewmentioning
confidence: 99%
“…However, like any technological advance, there are unintended consequences of this rapidly available information. Studies have found chat rooms used for discussion of benzydamine abuse to induce hallucinations and fraudulent websites often target uneducated populations with desperate medical conditions (SOUZA, 2008;VASCONCELLOS-SILVA, 2011). …”
Section: Literature Reviewmentioning
confidence: 99%
“…One concerns the recurrent situations caused by improper conduct in the healing processes of some religious leaders regarding the vulnerability of their customers, who become involved in nefarious religious practices resulting in dissatisfaction, disappointment and the solidification of the social image of African matrix religions as "evil religions" or "evil practices." This situation is not exclusive to these religions, but it commonly appears in many emergent ones, even in the digital realm, as shown by the study by Vasconcellos et al (2011) on the use of the Internet as a tool for fraudulent propagation of therapeutic practices.…”
mentioning
confidence: 99%